Inovasi Manajemen Keuangan Melalui Cashless Payment di Pesantren Darussalam Blokagung Banyuwangi - Fitria, Ulfa (Universitas Negeri Malang, 2024)
Abstract: The adoption of cashless transactions in Indonesia and other aspects of society 5.0, along with the advancement of digital technology, are still to identify the cashless payment system as a novel approach to the Islamic boarding school Darussalam Blokagung Tegalsari Banyuwangi's financial management. The method used in this study is qualitative descriptive. Interview rules serve as a supporting instrument, and the researcher herself becomes an instrument (a human instrument). Data using methods such as documentation, interviewing, and observation. Data triangulation for data veracity. The investigation's findings are Four stages to establish the cashless payment system at the Darussalam Islamic Boarding School Blokagung Tegalsari Banyuwangi: identifying the innovation of the cashless payment system and interacting with vendors in the permanent setting, calculating the budget for the cashless payment system within the student expenditure budget, At the Islamic boarding school, the cashless payment system program is being implemented gradually. The boarding school's financial management was surveyed to evaluate still to the cashless payment system at the Darussalam Blokagung Banyuwangi Islamic Boarding School. Keywords: Financial Management, Cashless payment, Digital Technology, Islamic Boarding School Abstrak: Terlepas dari kemajuan teknologi digital ke era masyarakat 5.0, penerapan cashless payment di Indonesia masih dianggap rendah. Tujuan dari penelitian ini adalah untuk mengetahui metode pembayaran cashless menjadi inovasi dalam bidang manajemen keuangan di pondok pesantren Darussalam Blokagung Tegalsari Banyuwangi. Studi ini menggunakan pendekatan deskriptif kualitatif. Peneliti menjadi instrumen (human instrument) serta pendukung, seperti pedoman wawancara. Observasi, wawancara, dan dokumentasi digunakan untuk mengumpulkan data. Metode triangulasi memastikan keabsahan data. Hasil dari penelitian adalah Pondok Pesantren Darussalam Blokagung Tegalsari Banyuwangi menerapkan sistem cashless payment dengan empat proses yakni: Penentuan inovasi sistem cashless payment dengan adanya sosialisasi kepada para pedagang lingkungan pesantren, Penetapan anggaran sistem cashless payment dalam anggaran belanja bagi santri, Pelaksanaan program sistem cashless payment dilakukan secara bertahap di pesantren, Evaluasi pelaksanaan sistem cashless payment dengan survei oleh pengurus keuangan pondok mengenai pelaksanaan transaksi sistem cashless payment di Pondok Pesantren Darussalam Blokagung Banyuwangi. Kata kunci: Manajemen Keuangan, Cashless payment, Teknologi Digital, Pondok Pesantren